Biopotential multi-path current feedback instrumentation amplifier with automatic offset cancellation loop for resistive bridge microsensors - Laababid, Younes; El Khadiri, Karim; Tahiri, Ahmed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This study introduces a refined current feedback instrumentation amplifier (CFIA) specifically designed for amplifying biopotential signals that originate from resistive-bridge sensors. The proposed architecture uniquely incorporates a multipath chopper-stabilized CFIA which has been developed to minimize the effects of bridge offsets, while maintaining low power usage, high input impedance, and reduced noise characteristics. The engineering blueprint employs a ripple reduction loop (RRL) to mitigate output ripple caused by chopper up-modulation. To speed up offset cancellation and to limit the offset caused by bridge mismatch, an automatic offset cancellation loop (AOCL) circuit is integrated within the analog front end (AFE). Crafted using a conventional 0.18 µm CMOS process, the CFIA in this design provides adjustable gain between 20.35 dB to 55.14 dB, with a power supply rejection ratio (PSRR) and a common mode rejection ratio (CMRR) of 103 dB and 114 dB, respectively. The system demonstrates an input-referred noise (IRN) value of 16 ηV/√Hz at 200 Hz frequency, equivalent to a noise efficiency factor (NEF) of 5.18. Operating from a supply voltage of 1.8V, the AFE shows a power consumption of 291 μW.